Long-term efficacy and safety of inebilizumab in neuromyelitis optica spectrum disorder: Analysis of aquaporin-4–immunoglobulin G–seropositive participants taking inebilizumab for ⩾4 years in the N-MOmentum trial. (May 2022) - Rensel, Mary; Zabeti, Aram; Mealy, Maureen A; Cimbora, Daniel; She, Dewei; Drappa, Jorn; Katz, Eliezer
Background: Efficacy and safety of inebilizumab for treatment of neuromyelitis optica spectrum disorder in adults seropositive for aquaporin-4 (AQP4)–immunoglobulin (Ig) G were demonstrated in the 28-week randomized controlled period of the N-MOmentum study. Objective: To assess efficacy and safety of long-term inebilizumab treatment. Methods: Post hoc analysis was performed in 75 AQP4–IgG–seropositive participants receiving inebilizumab for ⩾4 years in the randomized controlled period and open-label extension of the N-MOmentum study. Results: Eighteen attacks occurred in 13 participants during inebilizumab treatment (annualized attack rate, 0.052 attacks/person-year). Twelve attacks occurred during the first year of treatment, and two each occurred in years 2–4. Disability scores remained stable throughout ⩾4 years of treatment. Inebilizumab was well tolerated, with two (2.7%) serious treatment-emergent adverse events related to inebilizumab and no deaths. Immunoglobulin G levels decreased over time; however, correlation between severe infections and low IgG levels could not be determined because of their small numbers. Conclusion: These results from the N-MOmentum study continue to support use of inebilizumab for treatment of neuromyelitis optica spectrum disorder. Furthermore, the findings suggest that efficacy of inebilizumab may be enhanced after the first year of treatment, warranting additional long-term investigation.